Pelatihan Bucket Snack Untuk Meningkatkan Kreativitas Dan Daya Saing Ibu-Ibu Rumah Tangga Di Sidoarjo - Sholikha Oktavi Khalifaturofi'ah; Zufra Inayah; Larasati Ayu Sekarsari (Pusat Riset dan Inovasi Nasional, 2023)
Skills training is an effective means to enhance the well-being of the community. In general, the residents of Sidoarjo, especially those who work as housewives, often lack competitiveness and creativity to empower themselves with their own abilities. This community engagement aims to boost the creativity and competitiveness of housewives in Sidoarjo. The activity is geared towards empowering housewives in Sidoarjo, particularly those who work as homemakers, to generate additional income through the production and sale of bucket snacks. The methodology employed involves participatory learning and action (PLA) characterized by socialization, direct discussions, and practical training. The outcome of this community engagement is the development of understanding and knowledge among housewives, enabling them to create bucket snacks and earn income from this skill. This initiative has resulted in the production of nine bucket snacks as a result of the training. The beneficiaries have reported an improved understanding of bucket snack production as a direct impact of this community engagement